SISTEM PENGAMBILAN KEPUTUSAN PENENTUAN PEMBERIAN BEASISWA DENGAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) : Studi Kasus : MIS Sirojul Athfal II - Uro Abdulrohim; Elip Abdullah; Indra Maulana Yusup Kusumah (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2018)
Decision support system (DSS) is a combination of individual intelligence sources with component capabilities to improve decision quality. Decision-making systems can also be described as systems capable of supporting ad hoc data analysis, and decision modeling, decision-oriented, future-planning orientation, and are used in unusual times. One of the methods used in making a decision-making system is the AHP (Analytic Hierarchy Process) method. AHP can be defined as a representation of a complex problem in a multi-level structure where the first level is the goal, followed by the level of factors, criteria, sub-criteria, and so on down to the last level of alternatives. With this scholarship decision-making system, it can help and facilitate MIS Sirojul Athfal II to assess students and determine students who are eligible for scholarships. The method applied in this system uses AHP (Analytic Hierarchy Process) because this method can assess a teacher based on the criteria that have been determined in detail in the stage of weighting the value of each criterion and its sub-criteria. Keywords: factors, Scholarship, Borland Delphi, Analytic Hierarchy Process, criteria